Investigation of six bioactive anthraquinones in slimming tea by accelerated solvent extraction and high performance capillary electrophoresis with diode-array detection. (15th May 2016) - Wang, Ning; Su, Ming; Liang, Shuxuan; Sun, Hanwen
Highlights: A capillary electrophoresis method is developed for analysis of six anthraquinones. Accelerated solvent extraction achieved rapidly and effectively sample preparation. The effective separation of six anthraquinones was achieved within runtime of 8 min. The developed method has speediness, high sensitivity, recovery and precision. The validated method can be applied for the quality control of slimming tea. Abstract: A rapid and effective method for effective separation and rapid simultaneous determination of six bioactive anthraquinones by capillary zone electrophoresis was developed. An accelerated solvent extraction procedure was used for the extraction of anthraquinones from slimming tea. Under the optimized conditions, the effective separation of six anthraquinones was achieved within 8 min. Good linearity was achieved, with a correlation coefficient ( r ) of ⩾0.999. The limit of detection ranged from 0.33 to 1.40 μg mL −1 . The intra- and inter-day relative standard deviation (RSD) of the six analytes was in the range of 2.3–3.9% and 3.2–4.9%, respectively. The average recovery of the six analytes from real tea samples was in the range of 86.15–98.30% with the RSD of 1.04–4.99%. The developed and validated method has speediness, high sensitivity, recovery and precision, and can be applied for the quality control of slimming tea.